2010
DOI: 10.1557/jmr.2010.0067
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of Young's modulus, shear modulus, and Poisson's ratio of soft hydrogels

Abstract: Besides biological and chemical cues, cellular behavior has been found to be affected by mechanical cues such as traction forces, surface topology, and in particular the mechanical properties of the substrate. The present study focuses on completely characterizing the bulk linear mechanical properties of such soft substrates, a good example of which are hydrogels. The complete characterization involves the measurement of Young's modulus, shear modulus, and Poisson's ratio of these hydrogels, which is achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 28 publications
7
42
0
Order By: Relevance
“…Most importantly, DNA gel design parameters can be controlled to mimic the stiffness of biological tissues. 6 This stringent control over design parameters and stiffness makes DNA gels a promising tool for applications in tissue engineering and cell-ECM modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, DNA gel design parameters can be controlled to mimic the stiffness of biological tissues. 6 This stringent control over design parameters and stiffness makes DNA gels a promising tool for applications in tissue engineering and cell-ECM modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The range of Poisson ratios, σ, that has been reported for polyacrylamide gels is between 0.3 and 0.49 [59] [60] [61]. The Young's modulus obtained in our experiments, assuming the Poisson ratio to be 0.3, has an average of E = 910 Pa and a standard deviation of 360 Pa.…”
Section: Traction Force Microscopy Methodsmentioning
confidence: 55%
“…ν is a measure of how a material contracts in the lateral dimension (lateral compressive strain) when stretched longitudinally (longitudinal extensional strain). The maximum ratio of 0.5 is found for some rubbers, which are termed incompressible, metals have a Poisson's ratio around 0.25 -0.35 (Pilkey, 2005) and hydrogels fall in an intermediate range of 0.38 to 0.49 (Chippada et al, 2010, Chen et al, 2013 Micromanipulation and Atomic Force Microscopy (AFM), shown schematically in Figure 2.6, are techniques that probe particle elasticity at a particular point on the particle surface.…”
Section: Rheology Above Maximum Packing Fractionmentioning
confidence: 99%
“…; and the number of nearest neighbours, n = 10 as determined by Rognon et al (2011) through discrete element simulation of packed suspensions of non-colloidal elastic spheres. Poisson's ratio is estimated based on the literature suggesting ν of hydrogels is dependent on cross-link density and falls in the range 0.38 to 0.49 (Chippada et al, 2010, Chen et al, 2013. Viscoelastic fluid behaviour is observed at φ rcp ≤ φ 0 ≤ φ j .…”
Section: Viscoelastic Solid-like Behaviour Above Jammingmentioning
confidence: 99%